2018
DOI: 10.1111/ocr.12242
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malocclusion in children with obstructive sleep apnoea

Abstract: This study showed a high prevalence of malocclusion in children with OSA compared to the control group. The posterior crossbite and deviations in overjet and overbite were significantly associated with OSA. The presence of these occlusal features shows the importance of an orthodontic evaluation in screening for paediatric OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 25 publications
3
14
1
10
Order By: Relevance
“…In this study, the occlusal variables showed a high frequency of malocclusion in mouth-breathing children similar to data from a recent study in children with obstructive sleep apnea 14 . This confirms that malocclusion is more frequent in mouth-breathing children compared to nasal breathers as reported previously 4 , 14 .…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the occlusal variables showed a high frequency of malocclusion in mouth-breathing children similar to data from a recent study in children with obstructive sleep apnea 14 . This confirms that malocclusion is more frequent in mouth-breathing children compared to nasal breathers as reported previously 4 , 14 .…”
Section: Discussionsupporting
confidence: 90%
“…As regards the presence of crossbite, while it has been correlated with respiratory disorders ( 9 , 12 , 14 ), our study found no statistically significant differences. In contrast, maxillary width was found to be significantly smaller in patients with SRBD, with a difference of 2.2 mm between patients with a low vs. moderate risk of SRBD.…”
Section: Discussioncontrasting
confidence: 74%
“…As discussed above, in patients where SRBD was associated with Class II malocclusion and open bite, this was usually accompanied by greater overjet and less overbite ( 8 , 14 ). Although greater overjet and less overbite were observed in our study in patients with positive questionnaire results, significant differences were only observed for the latter association.…”
Section: Discussionmentioning
confidence: 91%
“…In the PANIC study, 28 conducted on 491 Finnish children 6-8 years of age, children with crossbite had a 3.3 times higher risk of having SDB (based on a questionnaire) than those without crossbite, and children with a convex facial profile had a 2.6 times higher risk of having SDB than those with a normal facial profile. A recent Italian study, 29 comparing a group of 139 children with OSA to a control group of 137 children (range 2-10 years, all diagnosed with PSG), described several orthodontic factors independently associated with OSA: posterior crossbite (odds ratio = 3.38), reduced overbite (odds ratio = 2.43), increased overbite (odds ratio = 2.19), and increased overjet (odds ratio = 4.25).…”
Section: Discussionmentioning
confidence: 99%